Myocardial infarction in an adult with cystic fibrosis and heart and lung transplant - Eaden, James; Peckham, Daniel (Multidisciplinary Respiratory Medicine, 2013)
We present a case of myocardial infarction in a 19 year old female with cystic fibrosis who had a heart and lung transplant performed at the age of four years old. She presented atypically with a one day history of severe, intermittent, central, sharp chest pain, radiating to her back and down her left arm. A coronary angiogram showed proximal stenosis of the left anterior descending artery and right coronary artery. She was treated with percutaneous coronary intervention, involving drug eluting stents to the left anterior descending artery (LAD) and the right coronary artery (RCA). In this study we discuss the pathophysiology, investigations and treatment of cardiac transplant vasculopathy. Although complete reversal of LAD and RCA stenosis was achieved, routine followup with coronary angiography and careful control of cardiac risk factors will be important to identify and reduce future restenosis and adverse cardiac events.